Confronting recent history: forced mobilization in Serbia during the war in Croatia 1991–1995 - Mladenov Jovanović, Srđan (Balcanica Posnaniensia. Acta et studia, 2020)
However much interest the Yugoslav conflicts of the nineties seem to have sparked within the broader academic community, some relevant topics are still found to be missing or underresearched. The forced mobilization during the Milošević regime that culled men of almost all age in order for them to fight for their country is one of them. With the recently published Untold stories of the victims of the forced mobilization, some new light has been shed on the cullings of the 1990s. This article explores those stories, including recently emerged transcripts from the governmental sessions discussing them, and puts them through a historical lens.